A study of the connection between gambling and crime in Hungarian prisons. (July 2016) - Tessényi, Judit; Kovács, Péter
Abstract: In the following study, we examine the connection between crime and gambling addictions. In addition to examining the playing habits of 140 detainees prior to their imprisonment, we also study their demographic characteristics, and their relations. 2 We previously studied these correlations as a part of a data recording in 2009 (Tessényi-Kovács, 2011). 3 By the 10th of October 2012, the use of gaming machines was terminated in Hungary. Therefore, our survey has gained a repeated actuality, since a significant cause of addiction has disappeared from the market. We question whether this factor has had a measurable effect. Although the elapsed time is not necessarily enough to measure the presumed changes in crime due to gambling, we nevertheless make the comparison with the results from 2009. For the study of pathological problem gambling, we applied the original version of the SOGS-questionnaire, complemented with demographics and other relevant questions from the perspective of our survey.